2020
DOI: 10.1088/1748-9326/ab9c4e
|View full text |Cite
|
Sign up to set email alerts
|

Climate, snowmelt dynamics and atmospheric deposition interact to control dissolved organic carbon export from a northern forest stream over 26 years

Abstract: Increasing concentrations of dissolved organic carbon (DOC) have been identified in many freshwater systems over the last three decades. Studies have generally nominated atmospheric deposition as the key driver of this trend, with changes in climatic factors also contributing. However, there is still much uncertainty concerning net effects of these drivers on DOC concentrations and export dynamics. Changes in climate and climate mediated snowfall dynamics in northern latitudes have not been widely considered a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…The Headwaters watershed also has experienced rising temperatures and precipitation (Motew and Kucharik 2013; https://nca2018.globalchange.gov/chapter/2/), and declining atmospheric deposition of sulfate, factors which have been shown to increase DOM mobilization and transport elsewhere. Despite conditions potentially conducive to increasing DOM and evidence for increasing DOC at two long‐term stream study sites in the region (Urban et al 2011; Meingast et al 2020), the record examined here showed only limited evidence for long‐term changes in annualized measures of color (CDOM) in the river. In‐depth analysis (Fig.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The Headwaters watershed also has experienced rising temperatures and precipitation (Motew and Kucharik 2013; https://nca2018.globalchange.gov/chapter/2/), and declining atmospheric deposition of sulfate, factors which have been shown to increase DOM mobilization and transport elsewhere. Despite conditions potentially conducive to increasing DOM and evidence for increasing DOC at two long‐term stream study sites in the region (Urban et al 2011; Meingast et al 2020), the record examined here showed only limited evidence for long‐term changes in annualized measures of color (CDOM) in the river. In‐depth analysis (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…Small watersheds in Ontario showed long‐term increases in DOC concentrations but not annual flux (Eimers et al 2008), and acid‐sensitive lakes in heavily acidified watersheds have increased in DOC and color following reduction in acidification compared to reference watersheds (Meyer‐Jacob et al 2020). A small watershed draining wetland and upland forest in central Minnesota showed long‐term increases in DOC (Urban et al 2011), and a small watershed in northern Michigan showed long‐term increases in both DOC concentration and annual flux (Meingast et al 2020). Together these studies support our findings that DOM changes in watersheds are controlled by complex processes, including strong influence by climate variability.…”
Section: Discussionmentioning
confidence: 99%
“…For example, changing growing seasons could alter rates of primary production (Barnett et al, 2005;Backlund et al, 2008;Christiansen et al, 2011), which can in turn alter N availability (Roberts and Mulholland, 2007), which our analyses identified as an important explanatory variable for denitrification and N 2 fixation rate. DOC concentrations, which was also related to denitrification and N 2 fixation in our analyses, are increasing in northern temperate streams globally due to decreases in sulfur deposition, increased temperatures, and increased precipitation (Roulet and Moore, 2006;de Wit et al, 2016); however, longterm changes in DOC concentrations in streams in the Upper Peninsula of Michigan, where this study was located, are less clear (Marcarelli et al, 2019;Meingast et al, 2020). Yet, each of these environmental drivers explained a relatively small proportion of the variation in process rates, which poses a challenge for predicting the responses of N cycling processes that could result from these changes.…”
Section: Daily Variation In N 2 Fixation and Denitrification Rates An...mentioning
confidence: 60%
“…During certain time periods, some sampling dates were skipped (Table 1) due to unsafe conditions such as extreme cold, storms, and high discharge. For this study, seasonality was determined using a combination of canopy cover, temperature, and discharge rather than calendar date, as the Upper Peninsula of Michigan experiences an extended winter period with substantial snowpack and short, rapidly changing spring and fall seasons (Coble et al, 2019;Meingast et al, 2020). Spring was determined to start when the river surface was no longer covered by ice and discharge was high due to snow melt, around late April or early May.…”
Section: Study Site and Sampling Designmentioning
confidence: 99%
“…The snow cover is the main source of annual runoff water in summertime in northern territories, controls the export dynamics of nutrients, and dissolved organic carbon (DOC). Changes in the hydrological cycles should inevitably modify concentrations and removal of chemical elements in the waters, including suspending matter, DOC and nutrients, [25]. Climate warming should change (with regard to the predictions) the time and intensity of snow melting, which in turn, should change the runoff to the lakes and marginal seas.…”
Section: Effect Of Climate Warming On Aquatic Systemsmentioning
confidence: 99%